Management of Character Education in the Scope of Elementary School Students in the Distance Learning Period - Riyanto, Muhammad; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Universitas Pendidikan Indonesia (UPI), 2022)
The increasingly rapid era of globalization coupled with this pandemic situation, many negative influences received by elementary school students both from social media or the environment, coupled with the current pandemic situation which requires distance learning which has an impact on the absence of direct practice from teachers or instructors about character education, which causes school students to lack character, character, and spirit of nationalism. The aim of the research is for elementary school students to understand character education and be able to practice it in daily life. The method used in this study is a quantitative approach, namely by giving pretest-posttest questions to determine the level of understanding of character education. The results of this study are still many students who do not understand character education. This character education will provide learning for students to understand what character, virtuous character, and spirit of nationalism are and instill in their daily lives.